Estimating Reference Evapo- transpiration in Mosul (Iraq) Using Cascade Neural Networks - Fatin Mahmoud Shehab; Raid Rafi Omar; Radhwan Yousif Sedik (Engineering and Technology Journal, 2014)
Recently artificial neural network (ANN) has been applied for estimating reference evapo-transpiration (ETₒ).In this study a mathematical model was built by application the cascade forward network technique (CCANN) to estimate the daily reference evapo-transpiration in the city of Mosul, north of Iraq .The input parameters for the CCANN were the: temperature, solar radiation, wind speed at 2m height, and relative humidity. A check for the accuracy of the performance of the network was made using values of reference evapo-transpiration obtained from pan evaporation method. The results revealed linear correlation between the network output and the data of the measured pan evapo-transpiration with correlation coefficient of (0.9679). This indicates the possibility of use of CCANN to determine the daily reference evapo- transpiration. The results also show that the CCANN model performs better more accurate compared to other models.